Dispositions and democratic educational reform - Thornton, Holly (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
Obecne reformy szkolne w USA w większości koncentrują się na odpowiedzialności, pod etykietą testowania wyników pracy nauczycieli. Bywa że konsekwencją takiego kierunku jest spłaszczanie programów nauczania do obserwowalnych zachowań uczniowskich, a tym samym do opanowywania przez uczniów oderwanych od siebie pojęć czy umiejętności. Implikuje to także styl pracy nauczycieli, którzy stają się bardziej technikami nauczania, określającymi szczegółowe postępowanie uczniów w procesie uczenia się. Obecnie w USA obserwuje się działania szkół przeciwne jednostronnemu ograniczaniu pomiaru wyników nauczania do obserwowalnych zachowań na rzecz działania wspierającego rozwój uczniów. Z badań wynika, że takie szkoły odnoszą także akademickie sukcesy mierzone testami oraz zaangażowaniem uczniów w uczenie się. Jednakże przede wszystkim zorientowanie szkoły na rozwój uczniów pociąga za sobą konsolidację współpracy zespołu nauczycielskiego.

Current educational reform efforts underway across the United States tend to focus on mandates including national curricula and national testing labeled an accountability movement, assuring that no child is left behind. The often unarticulated consequence of this movement has been a narrowing of the curriculum and pressure to make certain often isolated and disconnected facts and concepts are covered in time to not only meet end of grade timelines, but often benchmark testing throughout the school year. Teachers find themselves acting more as technicians following prompts, pacing guides, and pre-packaged materials rather than relying on their professional education, expertise, and instincts. They feel limited in employing what they know helps students to learn not only information, but deep understanding and ultimately what it means to be a positive member of the school society and our future democracy. The belief that technical “how to” knowledge is sufficient for producing teacher excellence is a false one (Collinson,1999) that is being perpetuated by No Child Left Behind (2005) and limiting exemplary teachers in terms of pedagogy that may move student achievement far beyond the limits of accountability testing. Related proposals for educational “reform” such as vouchers, charter school management companies, national mandates for statewide curricula standards, and high stakes testing may be well intended, but may actually exacerbate inequalities, and may cause us both to misrecognize what actually produces difficult social and educational problems and perhaps to miss some important democratic alternatives that may offer more hope for true reform in the long run (Apple, 2000; Apple, 2001; Apple & Beane, 1999).
Dyspozycje i demokratyczne reformy szkolne
Keywords: Dyspozycje; Dispositions; Reforma; Reform; Szkoła; School; edukacja; education; Neodidagmata; Technical teaching; Technicy nauczania